1984
DOI: 10.2337/diab.33.6.604
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Polyol Accumulation in Diabetes and its Prevention by Oral Sorbinil

Abstract: SUMMARYAlthough enhanced activity of the polyol pathway has been implicated in the pathogenesis of certain complications of diabetes, evidence that aldose reductase activity and sorbitol content are increased in the characteristic tissue site of the diabetic renal lesion has been lacking. We therefore measured polyols in glomeruli isolated from control and streptozotocin-diabetic rats, and assessed whether changes in diabetic glomeruli could be prevented by oral administration of the aldose reductase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(28 citation statements)
references
References 7 publications
1
26
1
Order By: Relevance
“…The result is an increase in tissue damage. The kidney is one of the target organs affected by oxidative stress in diabetes (Beyer-Mears et al, 1984;Bell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The result is an increase in tissue damage. The kidney is one of the target organs affected by oxidative stress in diabetes (Beyer-Mears et al, 1984;Bell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes of the polyol pathway, aldose reductase and sorbitol dehydrogenase, have been identified in glomerular cells including mesangial cells [26]. Furthermore, sorbitol accumulation has been found in glomeruli isolated from streptozotocin (STZ)-diabetic rats, and this change is considered to result in the myoinositol depletion and subsequent impairment of Na/K-ATPase activity found in diabetic glomeruli [27,28]. It is observed that a high-glucose condition per se is able to cause sorbitol accumulation and myoinositol depletion in cultured rat mesangial cells [29].…”
Section: Activation Of the Polyol Pathwaymentioning
confidence: 98%
“…A common mechanism by which glucose modulates cell function is by increased polyol pathway activity [33, 34, 35]. Metabolism of glucose by the polyol pathway consists of two reactions (fig.…”
Section: Discussionmentioning
confidence: 99%